Relevansi Rasionalitas Mu'tazilah dalam Pembelajaran Pendidikan Agama Islam - Achmad Junaidi; Mohammad Madani; Maimun (Kartika: Jurnal Studi Keislaman, 2026)
This study aims to analyze the construction of Mu'tazilite rationality in the Akidah Akhlak textbook and Muktafi's thought, as well as to examine its relevance to Islamic Religious Education (IRE) learning. This research employs a qualitative approach with library research type using content analysis method. The primary data sources consist of the Akidah Akhlak textbook for Madrasah Aliyah and Muktafi's work Tauhid dan Pemikiran Kalam, while supporting data are obtained from various relevant scholarly literatures. The findings reveal that the construction of Mu'tazilite rationality is built upon four main dimensions, namely reason as an epistemological foundation, human freedom and moral responsibility as an ethical foundation, divine justice as a theological foundation, and critical rationality in understanding revelation as a methodological foundation. The analysis also indicates a dialectic between rationality and humanity in the history of Mu'tazilah, particularly through reflection on the Mihnah event which shows that rationality without respect for freedom of thought has the potential to produce intellectual authoritarianism. In the context of IRE learning, the values of Mu'tazilite rationality are relevant for developing critical thinking skills, moral responsibility, a culture of dialogue, moderate attitudes, and respect for diversity of views.